Medical Students’ Experiences with Social Determinants of Health in Medical Education in Rwanda: A Qualitative Study - Swedberg CO; Abate Lemu E; Uwantege Giraneza C; Bradley EH (Advances in Medical Education and Practice)
Claire O Swedberg,1,* Eden Abate Lemu,1,* Christelle Uwantege Giraneza,1,* Elizabeth H Bradley2,* 1University of Global Health Equity, Butaro, Rwanda; 2Vassar College, Poughkeepsie, NY, USA*These authors contributed equally to this workCorrespondence: Claire O Swedberg, Email coswedberg@gmail.comBackground: Despite growing recognition of the importance of social determinants of health in medical practice, physician training in this area remains limited. The aim of this research was to evaluate medical students’ experiences with an innovative, social determinants of health-focused curriculum at the University of Global Health Equity (UGHE) in Rwanda, where social medicine is embedded in the Bachelor of Medicine, Bachelor of Surgery (MBBS) program.Methods: This was a qualitative study using data from in-depth interviews (n=18). We used the constant comparative method of data analysis to characterize recurrent themes across the interviews.Results: Four recurrent themes in students’ experiences with the social determinants of health-focused curriculum emerged: 1) increased students’ self-awareness about their own biases, 2) moved students from a mode of blame to a practice of empathy 3) allowed students to see patients as whole people with complex stories and needs rather than merely a diagnosis or set of diseases, and 4) strengthened students’ commitment to addressing shortcomings in the larger health system as part of improving health.Conclusion: Our study adds to the literature by demonstrating the potential for medical schools in low-income settings to implement social determinants of health into their curriculum. Findings from the study may be useful for medical educators and policymakers seeking to implement more holistic approaches to medical education.Keywords: social determinants of health, medical education, Africa, social sciences